A study of knowledge and practice for disposal of unused and expired pharmaceuticals among medical undergraduates at tertiary care teaching hospitals in Uttar Pradesh, India - Jindal, Meenakshi; Goel, Raj Kumar (International Journal of Basic & Clinical Pharmacology, 2018)
Background: Increasing disease incidence and prevalence necessitate healthcare practitioners to prescribe diverse medications. Families and patients are in possession of unused or expired medications and its risks have started gaining notice across the world. Majority of them including medical students are unaware about the disposal of unused or expired medicines. Misuse and improper disposal of unused/expired medications is a major safety and environmental concern, and thus proper disposal of those medications is highly important. Methods: Questionnaire based study was conducted among medical undergraduates of third year MBBS in two tertiary care teaching hospitals of Uttar Pradesh after approval from Institutional Ethical Committees during July-August 2018. Results: There were 65% of respondent had unused drugs in their home while 30% had the expired drugs. The most common reason for the unused and expiry drugs in the home was self-discontinuation. Analgesics were the main group of drugs possessed by participants. 67% in this study responded that drug disposal method was disposing the expired drugs to garbage. Only 26% know about the area in the city where unused/expired drugs are collected. 46% think that proper education of the community is required for appropriate disposal of unused drugs. Conclusions: Intervention by education about prudent drug disposal techniques that are also environmentally safe and acceptable is the need of time to change their behavior. There is also needing to understand the practice and awareness of the public to make any such education by program a success.